A cultural approach of embedding KPIs into organisational practices - Zakaria, Zamzulaila (Emerald Group Publishing Limited, 2015)
Abstract Purpose – The purpose of this paper is to discuss the ways in which organisations embedding key performance indicators (KPIs) as part of their organisational activities. Specifically this paper shows the role of cultural change programme in enabling the implementation of KPIs in the context of this study. Design/methodology/approach – The present study was conducted using ethnographic approach. Consistent with tradition in doing ethnographic studies, observation was the main method employed in this study. Additionally, this study employed interview and document review methods. Findings – This study concludes that the operation of KPIs in this organisation were made to work through a programme of cultural change. This finding suggests that accounting measurements such as KPIs can be embedded as part of organisational activities through cultural intervention. Practical implications – This study provides empirical evidence of the actions people do in making performance measurement works in organisations. Originality/value – This study adds to the limited number of literatures that link culture and performance measurement.